(untitled) (Journal of Student Affairs in Africa, 2023)
Abstract University students were regarded as a vulnerable population, who endured greater levels of mental health problems and financial distress in addition to the academic challenges of transitioning to online learning methodologies during the COVID-19 pandemic. Hence, the tumultuous nature of the pandemic and consequent sheltering in place and other disruptions placed a huger burden on this vulnerable population. Using qualitative research methodologies, this study sought to explore the challenges faced by students, through the lens of social workers who were placed at a University of Technology during the pandemic. Using purposive sampling techniques to recruit these practitioners the study further sought to enquire about what support measures were required to be in place, to enhance the well-being of students during the pandemic. Data was collected using semi-structured interviews and the analysis was guided by thematic analysis. The study found that students encountered an array of psychological problems, together with experiences of stigma, isolation whilst in quarantine which led the sample to call for the reconstruction of the university space into a more supportive one.